Early prehistoric activity: discussion (Scottish Historical and Archaeological Internet Reports, 2007)
The disarticulated skeletons represent the primary burials within each cist. These remains were disturbed and redeposited over the The main focus of the discussion is on the nature of the burial practice represented by the cists and the possible sequence of events that led to their final form. Three hypotheses are presented. remainThe disarticulated skeletons represent the primary burials within each cist. These remains were disturbed and redeposited over the remains of secondary articulated burials within each cist. This hypothesis requires two separate acts of burial activity. Each cist contains two skeletons, reflecting a single burial event. This implies that in each case a corpse was interred along with the defleshed remains of a second individual. The disarticulated remains represent secondary burials within each cist. This hypothesis requires two burial events.